2015
DOI: 10.1111/psj.12102
|View full text |Cite
|
Sign up to set email alerts
|

Reassessing “City Limits” in Urban Public Policy

Abstract: Urban public policy continues to explore the problems of urban growth and decline in a multidisciplinary fashion, focusing multiple theoretical lenses on questions of governance and division of authority as well as the practical applications for areas of policy specialization. This article reviews recent articles on income, housing, and racial/ethnic stratification, which share a common link of mobility‐based prescriptions. It also reviews the role sustainability, equity, and cultural norms play in scholarship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 100 publications
(93 reference statements)
0
2
0
Order By: Relevance
“…Under this scenario, developmental policy includes not only satisfying the needs of businesses but also establishing the urban amenities that attract a desirable workforce (Clark et al 2002). This group is drawn to city life because of urban diversity, tolerant attitudes, compact neighborhoods served by mass transit, and abundant social and cultural activities (Deslatte 2015, S69–70; Florida 2003; Sharp 2005).…”
Section: Income Inequality and Citiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Under this scenario, developmental policy includes not only satisfying the needs of businesses but also establishing the urban amenities that attract a desirable workforce (Clark et al 2002). This group is drawn to city life because of urban diversity, tolerant attitudes, compact neighborhoods served by mass transit, and abundant social and cultural activities (Deslatte 2015, S69–70; Florida 2003; Sharp 2005).…”
Section: Income Inequality and Citiesmentioning
confidence: 99%
“…The income gap between these groups has the potential to lead to policy conflict. However, research has shown that a new political culture has developed in some cities that places a value on addressing postmaterial issues such as income inequality (Deleon and Naff 2004; Deslatte 2015; Sharp 2005). This article examines whether redistributive issues relating to income inequality and the poor are part of current mayoral agendas or whether traditional issues of economic development still predominate.…”
Section: Introductionmentioning
confidence: 99%